2019
DOI: 10.3390/cryst9120658
|View full text |Cite
|
Sign up to set email alerts
|

High Efficient YVPO4 Luminescent Materials Activated by Europium

Abstract: YPO4:Eu, YVO4:Eu, and YVPO4:Eu based phosphors with various Eu(III) activator contents and phosphate-vanadate ratios were synthesized by the self-propagating high-temperature synthesis method. The samples were characterized by scanning electron microscopy, nitrogen sorption, acid-base indicators and photoluminescence. The particle surface features with a finely dispersed structure comprising all the involved elements. The pore structure and the specific surface areas of the samples were different depending on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Minakova et al have shown that the peak related to the (220) plane was split. In this case, there could be indicated the existence of another crystal phase in the YV x As 1– x O 4 matrix . Therefore, an emergence of the double-exponential decay profile could be seen, when such a phenomenon occurs.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Minakova et al have shown that the peak related to the (220) plane was split. In this case, there could be indicated the existence of another crystal phase in the YV x As 1– x O 4 matrix . Therefore, an emergence of the double-exponential decay profile could be seen, when such a phenomenon occurs.…”
Section: Resultsmentioning
confidence: 88%
“…The decays present In this case, there could be indicated the existence of another crystal phase in the YV x As 1−x O 4 matrix. 36 Therefore, an emergence of the doubleexponential decay profile could be seen, when such a phenomenon occurs. The short time component can be associated with the Tb 3+ :YV x As 1−x O 4 phase in which Tb 3+ ions are nearby V 5+ ions as well as As 5+ ions.…”
Section: Resultsmentioning
confidence: 99%
“…YPO 4 is considered as one of the best host material to prepare luminescent compounds, since they acquire high quantum efficiency and because of the existence of explicit absorption and emission spectral regions . High absorption and high vacuum stability during the radiation process in the ultraviolet (UV) domain make them as an efficient source of red light in normal and plasma display process . Eu 3+ -doped YPO 4 was reported to have the aforementioned quality; hence the possibility of using the material as a red light-emissive source was proposed by Chanchan and Singh .…”
Section: Introductionmentioning
confidence: 99%
“… 21 High absorption and high vacuum stability during the radiation process in the ultraviolet (UV) domain make them as an efficient source of red light in normal and plasma display process. 22 Eu 3+ -doped YPO 4 was reported to have the aforementioned quality; hence the possibility of using the material as a red light-emissive source was proposed by Chanchan and Singh. 21 Due to its high thermal expansion coefficient, it was explored as green barrier coatings to protect silicon ceramics.…”
Section: Introductionmentioning
confidence: 99%